2007
DOI: 10.1051/0004-6361:20078435
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Galactic synchrotron emission on CMB anisotropy measurements

Abstract: Context. Galactic foreground emission fluctuations are a limiting factor for precise cosmic microwave background (CMB) anisotropy measurements. Aims. We intend to improve current estimates of the influence of Galactic synchrotron emission on the analysis of CMB anisotropies. Methods. We perform an angular power spectrum analysis (APS) of all-sky total intensity maps at 408 MHz and 1420 MHz, which are dominated by synchrotron emission out of the Galactic plane. We subtract the brighter sources from the maps, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
73
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 50 publications
10
73
0
Order By: Relevance
“…The slope is within the range of slopes [-2, -3] found by all the previous measurements at higher frequencies (Tegmark & Efstathiou 1996;Giardino et al 2001;Bennett et al 2003;La Porta et al 2008).…”
Section: Power Spectrum Analysissupporting
confidence: 83%
See 2 more Smart Citations
“…The slope is within the range of slopes [-2, -3] found by all the previous measurements at higher frequencies (Tegmark & Efstathiou 1996;Giardino et al 2001;Bennett et al 2003;La Porta et al 2008).…”
Section: Power Spectrum Analysissupporting
confidence: 83%
“…At large angular scales there is a power-law behaviour, with power decreasing at increasing angular scale. This behaviour is typical of the Galactic diffuse emission observed at higher frequencies and higher angular resolutions (Bennett et al 2003;La Porta et al 2008).…”
Section: Power Spectrum Analysissupporting
confidence: 56%
See 1 more Smart Citation
“…The analysis of synchrotron fluctuations deals with magnetic fluctuations, and previous studies of the angular power spectrum of the Galactic radio diffuse synchrotron emission (see e.g. Giardino et al 2001;La Porta et al 2008) have shown it can be fitted by a power law, C l ∝ l α , with α ∼ [−3.0, −2.5] and l 200. Moreover, strong local variations in the index exist.…”
Section: Discussionmentioning
confidence: 99%
“…Radio frequency information such as the Leiden 408 MHz and 1.4 GHz surveys (Brouw & Spoelstra 1976;Wolleben et al 2006), the Parkes survey at 2.4 GHz (Duncan et al 1999), and the MGLS survey (Medium Galactic Latitude Survey) at 1.4 GHz (Uyaniker et al 1999) are generally used to provide insight the Galactic diffuse synchrotron emission in polarized intensity. However, Faraday rotation introduces complications into the interpretation of such data since strong depolarization is expected for frequencies lower than 10 GHz (Burn 1966;Sun et al 2008;Jaffe et al 2010;Jansson et al 2009;La Porta et al 2008, 2006. Consequently, the best polarized Galactic diffuse synchrotron tracers are at high frequency such as the Wmap survey at 23 GHz (Page et al 2007).…”
Section: Diffuse Galactic Synchrotron Emissionmentioning
confidence: 99%